2014
DOI: 10.1108/ijbm-03-2014-0042
|View full text |Cite
|
Sign up to set email alerts
|

How to recover trust in the banking industry? A game theory approach to empirical analyses of bank and corporate customer relationships

Abstract: Purpose -Trust is a crucial element of a viable banking industry. In the corporate market though, the characteristics of the relationships between each corporate customer and the bank is a double-sided problem. Both parties might trust the other or choose to behave opportunistically. The paper aims to discuss these issues. Design/methodology/approach -The authors have analyzed the effects of inter-organizational trust and opportunism on the perception of risk. The paper presents a structural equations model ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
4
33
0
1
Order By: Relevance
“…Customer trust influences customer loyalty, so the higher the customer trust is, the higher is the customer loyalty (Bagram, 2010;Jarvinen, 2014;Paulssen, Roulet, & Wilke, 2014). Many researchers have considered the role of trust in development of quality relationship (Dahlstrom, Nygaard, Kimasheva, & Ulvnes, 2014) along with customer satisfaction. Trust has also been conceptualized as a powerful feature of relationship management (Anderson, Lodish, & Weitz, 1987), a source of believability and honesty (Zeithaml, Barry, & Parasuraman, 1996) and a tool of communication between parties.…”
Section: Impact Of Customer Trust On Customer Loyaltymentioning
confidence: 99%
“…Customer trust influences customer loyalty, so the higher the customer trust is, the higher is the customer loyalty (Bagram, 2010;Jarvinen, 2014;Paulssen, Roulet, & Wilke, 2014). Many researchers have considered the role of trust in development of quality relationship (Dahlstrom, Nygaard, Kimasheva, & Ulvnes, 2014) along with customer satisfaction. Trust has also been conceptualized as a powerful feature of relationship management (Anderson, Lodish, & Weitz, 1987), a source of believability and honesty (Zeithaml, Barry, & Parasuraman, 1996) and a tool of communication between parties.…”
Section: Impact Of Customer Trust On Customer Loyaltymentioning
confidence: 99%
“…At the core of the banking industry relationships with its customers is the element of trust. Dahlstrom et al (2014) explored how trust interacts with, and is compromised by, other values challenging the banking-client relationship. They surveyed bank executives and their customers and found that there is "an intriguing mixed strategy between trust for one party and opportunism for the other.…”
Section: Banking Industrymentioning
confidence: 99%
“…The subprime crisis that started in the spring of 2007 on the Anglo-Saxon mortgage markets was primarily due to household overlending, and due to banks' normative behaviour in the lending market, it soon spread globally. As an inevitable concomitant, the amount of defaulted loans rocketed (Agarwal et al, 2014;Dahlstrom, 2014). Although the expansion of budget sectors and central banks solved the liquidity and capitalisation-related problems of commercial banks struggling with problematic loan portfolios, banks practising more prudent lending and households using credits more consciously are considered as longer-term stabilising factors (Lentner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%